Responses to dietary supplementation with field bean (Vicia faba var. minor) in production indices, mohair growth and hormonal parameters in transition Angora goats. Issue 1 (31st December 2022) - Todini, Luca; Galbraith, Hugh; Malfatti, Alessandro; Acuti, Gabriele; Barbato, Olimpia; Antonini, Marco; Beghelli, Daniela; Trabalza-Marinucci, Massimo
Abstract: Twenty-two pluriparous single-foetus-bearing Angora goats, housed 3 weeks pre-partum in mid-December, and in transition from pregnancy to lactation were used to test the efficacy of post-partum supplementation (Group S: 11 goats) or not (Group C: 11 goats) with 300 g/head/day of whole field bean seeds (WFBS) to a diet based on mixed hay ad libitum and natural pasture. The goats were maintained with the suckling of their kids for 90 days. Significant decreases in liveweight (LW) and body condition score (BCS), were documented post-parturition in both groups and were then maintained throughout. These suggest a mobilisation in body tissue that was not mitigated by WFBS supplementation. However, the faster growth of the suckled kids and greater elongation of mohair fibre recorded (Group S > Group C), suggested improvement in partition towards production indices of lactation and hair fibre deposition, respectively. Greater concentrations of total thyroid hormones, T3 and T4 in supplemented does were recorded. Overall mean (pre-prandial) plasma insulin concentrations, not different between treatments, decreased ( p < 0.5) from pre-partum concentration, and showed a pattern in time, similar to that of LW and BCS. Insulin appeared not to contribute to the suggested lactational and hair growth effects and possibly contributed to transition by a homeorhetic-type reduction in concentration post-partum. Mean plasma insulin-like growth factor-1 (IGF-1) concentrations trended lower due to supplementation from 3 weeks after kidding. It is concluded that WFBS supplementation was efficacious in improving production indices of the transition Angora goats. The feeding of different quantities of WFBS should be investigated. HIGHLIGHTS: Supplementation of transition Angora goats with field bean did not affect the loss of body weight or body condition score occurring after kidding. Supplementation with field bean induced higher concentrations of blood thyroid hormones, without affecting post-partum reductions in insulin. Supplemented dams had a greater mohair elongation rate and their kids grew more, by likely preferential partition to hair growth and lactation, rather than other body tissues.